Pharmacokinetics and physiologic effects of xylazine-ketamine-butorphanol administered intramuscularly or in combination with orally administered sodium salicylate on biomarkers of pain in Holstein calves following concurrent castration and dehorning - Baldridge, Sarah (Kansas State University, 2010)
Objective—To determine the pharmacokinetic parameters of xylazine, ketamine, and butorphanol administered IM and sodium salicylate administered PO and to compare their effect on biomarkers of pain and distress following sham (Period 1) and actual (Period 2) castration and dehorning. Animals—40 Holstein bull calves Procedures—Calves weighing 108 to 235 kg received the following treatments prior to sham castration and dehorning (Period 1) and castration and dehorning (Period 2) (n=10 calves/group): (i) 0.9% saline solution IM (PLACEBO) (ii) sodium salicylate (SAL) supplied free-choice in water to provide concentrations from 2.5 to 5 mg/mL beginning 24 hours prior to Period 1 to 48 hours after Period 2; (iii) 0.025 mg/kg butorphanol, 0.05 mg/kg xylazine, 0.1 mg/kg ketamine co-administered IM immediately prior to both periods (XKB); and (iv) a combination of treatments (ii) and (iii) (SAL + XKB). Plasma drug concentrations, average daily gain (ADG), chute exit speed, serum cortisol concentrations and electrodermal activity (EDA) were evaluated. Results—ADG (0-13d) was significantly greater in the SAL and SAL + XKB groups. Calves receiving XKB had significantly slower chute exit speed in both periods. Serum cortisol concentrations were significantly increased in all groups during Period 2 compared to Period 1. However, XKB attenuated serum cortisol response for the first hour after castration and dehorning while oral salicylate significantly reduced cortisol from 1-6 hours. XKB administration significantly decreased EDA scores in both periods. Conclusions and Clinical Relevance—Free-choice sodium salicylate decreases cortisol concentrations and reduced weight loss associated with castration and dehorning in calves.
Keywords: Welfare; Pain; Castration; Dehorning; Cattle; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473)